Treatment of Palm Oil Mill Effluent (POME) using electrolysis - Abu Sahit, Mohamad Imran; Kasmuri, Norhafezah; Zaini, Nurfadhilah (Universiti Teknologi MARA, Kedah, 2023)
Wastewater treatment is crucial to remove all the solids and contaminants in grey water before being discharged into the environment. This method is significant in safeguarding water quality and environmental ecosystems. It can be denoted that; the palm oil industry has become one of the valuable resources in Malaysia’s economic growth. Malaysia is one of the world’s largest producersof palm oil. Palm oil brings many benefits in terms of oil production and other products. However, these industry activities can cause environmental pollution. It has generated hazardous waste, namely palm oil mill effluent (POME), threatening human and aquatic life. POME is a brownish liquid, richin organic material and has an unpleasant odour. Over the past decade, wastewater treatment using electrolysis/electrocoagulation has been effective in various water treatment applications in urban and industrial wastewater treatment. Three objectives have been highlighted in this study. Firstly, to characterize POME, which contains high biochemical oxygen demands (BOD), chemical oxygen demands (COD), and suspended solids. Secondly, fabrication of the electrolysis reactor for treating POME. Lastly, to evaluate the quality of treated POME using the Environmental Quality Act 1974. The data obtained has proved the effectiveness of the electrolysis technique. The concentration of contaminants such as BOD, COD, total suspended solids, phosphorus, turbidity, ammonia-nitrogen, nitrite-nitrogen, and nitrate-nitrogen have decreased after the treatment.